A systematic review and critical appraisal of qualitative metasynthetic practice in public health to develop a taxonomy of operations of reciprocal translation. (28th July 2015) - Melendez‐Torres, G. J.; Grant, Sean; Bonell, Chris
Abstract : Introduction: Reciprocal translation, the understanding of one study's findings in terms of another's, is the foundation of most qualitative metasynthetic methods. In light of the proliferation of metasynthesis methods, the current review sought to create a taxonomy of operations of reciprocal translation using recently published qualitative metasyntheses. Methods: On 19 August 2013, MEDLINE, Embase and PsycINFO were searched. Included articles were full reports of metasyntheses of qualitative studies published in 2012 in English‐language peer‐reviewed journals. Two reviewers, working independently, screened records, assessed full texts for inclusion and extracted data on methods from each included metasynthesis. Systematic review methods used were summarised, and metasynthetic methods were inductively analysed to develop the taxonomy. Results: Of 61 included metasyntheses, 21 (34%) reported fully replicable search strategies and 51 (84%) critically appraised included studies. Based on methods in these metasyntheses, we developed a taxonomy of reciprocal translation with four overlapping categories: visual representation; key paper integration; data reduction and thematic extraction; and line‐by‐line coding. Discussion: This systematic review presents an update on methods and reporting currently used in qualitative metasynthesis. It also goes beyond the proliferation of approaches to offer a parsimonious approach to understanding how reciprocal translations are accomplished across metasynthetis methods. Copyright © 2015 John Wiley & Sons, Ltd.